Assessment of Metabolic Alterations Induced by Halogenated Additives and Antifungal Activity of Extracts from the Endophytic Fungus Fusarium sp. Associated with Dizygostemon riparius (Plantaginaceae) - Hilzimar de Jesus Freitas Sá; Anne Karoline Maiorana Santos; Adriano Souza Fonseca; Lourivaldo da Silva Santos; Josivan Regis Farias; Rosane Nassar Meireles Guerra; Edson Rodrigues-Filho; Gilmar Silverio da Silva; Cleydlenne Costa Vasconcelos; Alberto Jorge Oliveira Lopes; Antônio José Cantanhede Filho (Metabolites, 2025)
Background/Objectives: Endophytic fungi are valuable sources of bioactive compounds with potential therapeutic applications. This study aimed to evaluate the antifungal activity of secondary metabolites produced by Fusarium sp. isolated from Dizygostemon riparius, with particular focus on the impact of culture medium supplementation with halogenated and metallic additives on metabolite production. Methods: The fungus was cultivated in standard Czapek medium and media supplemented with NH4Br or MnCl2. Methanolic extracts were obtained, fractionated, and chemically characterised via LC-ESI-HRMS. In vitro antifungal assays, including MIC and MFC determinations and biofilm inhibition tests, were performed against Candida albicans strains. In vivo toxicity and efficacy were assessed using Tenebrio molitor larvae. Results: Fifteen metabolites were annotated, including known antifungals such as fusaric acid and cyclosporin A. Fractions EMBr4 and EMC5 demonstrated fungicidal activity with MIC values close to fluconazole and significantly inhibited biofilm formation and maturation. In vivo, these fractions displayed low acute toxicity and improved survival in infected larvae, comparable to fluconazole treatment. Conclusions: The results indicate that culture medium modulation enhances the production of bioactive metabolites by Fusarium sp., leading to extracts with notable antifungal efficacy and safety. EMBr4 and EMC5 are promising candidates for further development as antifungal agents, particularly for targeting biofilm-associated Candida infections. These findings support the potential of endophytic fungi as sources of novel therapeutics and warrant further mechanistic and pharmacological investigations.